Pengaruh Pemberian Promotif Media Panggung Boneka dan Cara Menyikat Gigi yang Benar terhadap Tingkat Pengetahuan Anak Prasekolah di TK Aisiyah Pangkajene - Arsad, Arsad; Asnuddin, Asnuddin; Alya, Alya; Tahir, Muhammad (Universitas Pahlawan Tuanku Tambusai, 2026)
The majority of children affected by dental caries reside in middle-income countries. Dental caries is the most common oral health problem, affecting 2 billion people with permanent teeth and 514 million children with primary teeth. This condition can negatively impact children’s quality of life, including eating, sleeping, and learning. To improve children’s knowledge of oral health, a structured and continuous intervention was implemented using puppet stage promotive media and proper toothbrushing techniques. The approach included community education, technology and science diffusion (IPTEKS), and practical training. Among 23 children, prior to the intervention, 10 children (43.5%) were categorized as good and 13 children (56.5%) as adequate. Following the intervention, 18 children (78.2%) were classified as good and 5 children (21.8%) as adequate. Statistical analysis revealed a p-value of 0.001, indicating a significant improvement in knowledge. These results demonstrate that puppet stage promotive media, delivered through a structured educational approach, effectively enhances children’s understanding of oral health and promotes healthy behaviors from an early age.